Teacher Skills in Preparing Evaluation Instruments: Case Study of Teacher’s Understanding to Construct Hots Instrument - Sastradika, Dedi; Risnita, Risnita; Al Farisi, Salman (Pendidikan Kimia Unimus, 2024)
Higher-order thinking Skills (HOTS) are 21st-century skills that must be facilitated in learning. However, currently, teachers are having problems understanding and designing HOTS skills instruments. This research aims to determine teachers' understanding in designing HOTS questions and determine the integrity of teachers' knowledge with instruments prepared by Social and Science subject teachers. This research is a mixed-method study with an Explanatory-Sequential Approach design. This research involved eight teachers with varied teaching experience. The results show that teachers lack understanding in preparing HOTS questions where the average achievement is 66.4% in every aspect of preparing HOTS questions. Analysis of the questions used by teachers shows that teachers still use questions at LOTS level (C1-C3). The interview results were coded using N-vivo, teachers had misconceptions about the development of HOTS questions and had different understandings in developing HOTS instruments. Future research can facilitate teachers to develop teachers' HOTS Instrument Preparation skills through training or workshops.